Analysis of thermal and dynamic comportment of a geothermal vertical U-tube heat exchanger - Bouhacina, Benamar; Saim, Rachid; Benzenine, Hamidou; Öztop, Hakan Fehmi (Elsevier Science Sa, 2013)
This paper presents a computational analysis on the turbulent flow and heat transfer for water flowing in a geothermal vertical U-tube heat exchanger (GHE). The governing equations, based on the k-epsilon model used to describe the turbulence phenomena, are solved by using finite volume method. The velocity and pressure terms of momentum equations are solved with SIMPLEC algorithm. The simulation of the dynamic and thermal behavior of the geothermal vertical U-tube heat exchanger was carried out under Fluent software. Results are compared with recent work from the literature and good agreement is obtained. The evolution of temperature and the heat transfer according to time (700h) and position, have been fixed, as well as the influence of fluid flow on the dynamic and thermal behavior of the heat exchanger. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Borehole temperature field; Numerical simulation; Thermal storage; U-vertical heat exchanger